APPLICATION OF THE INSTITUTE OF RECOGNITION AND ENFORCEMENT OF FOREIGN JUDGMENTS ON BANKRUPTCY IN ECONOMIC COURTS (European Journal of Economics, Finance and Business Development, 2025)
This article examines the main features of the regulation and problems of the functioning of the institution of transnational bankruptcy, as well as the problems of the lack of a mechanism for legal regulation of the recognition and enforcement of relevant judicial acts in the Republic of Uzbekistan. The author, based on the study of the legal regulation of the institution of recognition and enforcement of foreign judicial acts in insolvency (bankruptcy) cases in international practice and national legal orders, proposes prospects for the development of the national bankruptcy decision recognition regime.